Giant Heterometallic [Mn36Ni4]0/2− and [Mn32Co8] “Loops-of-Loops-and-Supertetrahedra” Molecular Aggregates - Charalambous, Maria; Moushi, Eleni E.; Nguyen, Tu N.; Papatriantafyllopoulou, Constantina; Nastopoulos, Vassilios; Christou, George; Tasiopoulos, Anastasios J. (Frontiers in Chemistry, 2019)
We report the synthesis, crystal structures and magnetic properties of the giant heterometallic [Mn36Ni4]2−/0 (compounds 1, 2)/[Mn32Co8] (compound 3) “loops-of-loops-and-supertetrahedra” molecular aggregates and of a [Mn2Ni6]2+ compound (cation of 4) that is structurally related with the cation co-crystallizing with the anion of 1. In particular, after the initial preparation and characterization of compound [Mn2Ni6(μ4-O)2(μ3-OH)3(μ3-Cl)3(O2CCH3)6(py)8]2+[Mn36Ni4(μ4-O)8(μ3-O)4(μ3-Cl)8Cl4(O2CCH3)26(pd)24(py)4]2− (1) we targeted the isolation of (i) both the cationic and the anionic aggregates of 1 in a discrete form and (ii) the Mn/Co analog of [Mn36Ni4]2− aggregate. Our synthetic efforts toward these directions afforded the discrete [Mn36Ni4] “loops-of-loops-and-supertetrahedra” aggregate [Mn36Ni4(μ4-O)8(μ3-O)4(μ3-Cl)8Cl2(O2CCH3)26(pd)24(py)4(H2O)2] (2), the heterometallic Mn/Co analog [Mn32Co8(μ4-O)8(μ3-O)4(μ3-Cl)8Cl2(μ2-OCH2CH3)2(O2CCH3)28(pd)22(py)6] (3) and the discrete [Mn2Ni6]2+ cation [Mn2Ni6(μ4-O)2(μ3-OH)4(μ3-Cl)2(O2CCH3)6(py)8](ClO4)(OH) (4). The structure of 1 consists of a mixed valence [Mn28IIIMn8IINi4II]2− molecular aggregate that contains two Mn8IIINi2II loops separated by two Mn6IIIMn4II supertetrahedral units and a [Mn2IIINi6II]2+ cation based on two [MnIIINi3II(μ4-O)(μ3-OH)1.5(μ3-Cl)1.5]4+ cubane sub-units connected through both mono- and tri-atomic bridges provided by the μ4-O2− and carboxylate anions. The structures of 2–4 are related to those of the compounds co-crystallized in 1 exhibiting however some differences that shall be discussed in detail in the manuscript. Magnetism studies revealed the presence of dominant ferromagnetic interactions in 1–3 that lead to large ground state spin (ST) values for the “loops-of-loops-and-supertetrahedra” aggregates and antiferromagnetic exchange interactions in 4 that lead to a low (and possibly zero) ST value. In particular, dc and ac magnetic susceptibility studies revealed that the discrete [Mn36Ni4] aggregate exhibits a large ST value ~ 26 but is not a new SMM. The ac magnetic susceptibility studies of the [Mn32Co8] analog revealed an extremely weak beginning of an out-of-phase tail indicating the presence of a very small relaxation barrier assignable to the anisotropic Co2+ions and a resulting out-of-phase ac signal whose peak is at very low T.